Quality of Green Space and Physical Health among Elderly People in Obio/Akpor Local Government Area, Rivers State: The Response of Psychology - P. W., Iyagba; Nnennaya. Q, Ogundipe (International Journal on Orange Technologies, 2022)
The study investigates quality of green space and physical health among elderly people in Obio/Akpor Local Government Area of Rivers State: The response of psychology. The study adopted a correlation research design with incident population of 7222 elderly in Obio-Akpor Local Government Area, Rivers State with a minimum sample of 367 representing 5% of the population. The study adopted 3 research questions and corresponding null hypotheses. Purposive random sampling technique was used to draw the minimum sample for the study. Three self-structured instruments were used for the study titled. Quality Green Space Scale (GSSS) and Physical Health Elderly Scale (PHES). The instruments 21 items with sub-sections, A, B, C and D. Section A with 5 items, B with 6 items and C with 5 items were used to elicit information from the respondents on the independent variable (GSSS), forest, private parks and private gardens while section D was used to elicit information on the dependent variable (PHES); Physical Health of the Elderly. The Instruments were subjected to experts in the department of Measurement and Evaluation, Faculty of Education, Ignatius Ajuru University, Rumuolumeni, Port Harcourt to validate the face and content of the instruments. Cronbach alpha was used to determine the internal consistency reliability coefficient of the instrument which measured 0. 78 and 0.85 respectively. The subscales forest 0.87, private parks 0.68, private gardens 0. 78. Linear regression was used to answer the research questions while t-test associated with linear regression was used to test the hypotheses at 0.05 level of significance. The study found out that there is a significant high positive relationship between green spaces; forest, private parks, private garden and physical health among the elderly in Obio/Akpor Local Government Area of Rivers State. Based on their response, it has shown that creation or recreations of green spaces are necessary for the physical health of the elderly in Obio/Akpor, Rivers State. The study recommended that residents should be sensitized on the benefits of green spaces in order to treat the green spaces with care. Government should create places for green spaces for the quality health of the inhabitants. Legislation against deforestation should be enacted to mark a point of sanction against reserved forest destruction.